ACTUAL INTAKE VERSES RECOMMENDED INTAKE AMONGST FEMALE ADOLESCENTS - Khalid, Memoona; Khan, Mahnaz Nasir; Kausar, Nasreen; Yousaf, Khadija; Khalid, Samia (European Scientific Journal, ESJ, 2014)
Background: The study was conducted to determine the dietary intake patterns of young females and to compare them with recommended servings. It was a descriptive quantitative study, in which a total of 100 girls of age 18-22 years participated from the Kinnaird College for Women, Lahore. Methods: Data was collected by taking dietary recall of the previous day using a 24 recall form. A food frequency questionnaire was also handed out to determine the dietary intake patterns and in order to validate the 24 hour recall. Before giving them a four day food diary which was collected after four days, they were explained about the serving sizes of different foods. Results: Approximately 50% of the respondents met the requirements of the food groups with the exception of vegetable group as only 2 % were taking according to the standards. When the validity of 24 hour with the food diary was checked, the insignificant p values being more than 0.05 indicated that their daily consumption was similar to the 24 hour recall. Conclusions: There should be more focus on eating a well balanced diet. Half of the young female adults are meeting the recommendations of the food groups with the exception of vegetable groups. It was concluded that the individuals had wrong perceptions about portion sizes and serving sizes thus awareness programs should also focus on that. A revised tool for the implementation of the dietary guidelines was recommended.